The Choco low‐level jet: past, present and future - Sierra, Juan P. (2021)
The Choco low-level jet is among the main regional circulation mechanisms related to the advection of water vapor from the eastern Pacifc to northwestern South America. Variations in the intensity of position of the jet core are identifed as determinant for regional moisture transport and associated rainfall. This paper analyzes the annual cycle of intensity and latitudinal location of this jet according to diferent reanalysis and observational datasets. Moreover, we compare possible changes in the Choco jet occurred during past climates, like the little ice age (LIA), with those associated with future scenarios of greenhouse gas concentrations (RCP8.5), using simulations from the Paleoclimate Modelling Intercomparison Project Phase 3 (PMIP3) and the Coupled Model Intercomparison Project Phase 5 (CMIP5). Our results suggest that according to reanalysis/observational data, as well as the CMIP5 models with the best representation of the Choco jet in present climate, there is a positive correlation between the jet intensity and its latitudinal location, and such relationship is associated with the sea level pressure (SLP) diference between the eastern tropical Pacifc and the northwestern South American landmass. Hence, stronger (weaker) SLP diferences favor a stronger (weaker) intensity and a northward (southward) location of the Choco jet. PMIP3 simulations suggest a stronger and northward Choco jet during LIA due to a stronger SLP diference in comparison to present climate. However, under the RCP8.5 scenario, there is not robust agreement among CMIP5 models although the best models suggest a southward jet at the end of the 21st century. This suggests that the mechanisms infuencing the Choco jet may play diferent roles during past natural climate changes with respect to anthropogenically-forced climate changes.